Na Śródce rewolucji nie było, czyli słabe więzi w procesie rewitalizacji - Dolata, Dorota (Człowiek i Społeczeństwo, 2012)
The term “weak ties” can be discussed in the context of both, interpersonal relationships in an anonymous metropolis and a mass society. Can the case of ródka in Pozna" be applied to certain questions relating to the phenomenon of weak ties? It is clearly visible, that revitalisation in this area of the city has lost its momentum now. Municipal program was a temporary way to avoid progressive degradation and increasing gentrification. However, in the most lively period of projects and events at ródka experts often referred to the traditional ties between inhabitants and invoked the urgency of their activities. Even the minimum effort and engagement was to trigger the renovation processes and contribute to the so-called sustainable development of ródka. It is worth asking at this point, who emphasized the role of local relations and animated the sequence of revitalizing events? What were the goals of revitalization animators? Did we come across the true cooperation of local residents, or perhaps the social participation was limited to the show for "tourists" from other parts of the city? Were the city officials able to engage the community of ródka? And if not the officials – were the artists able to (re)build relationships and connections between inhabitants? Their projects – both individual and group ones – are an important material for research To understand the growing complexity of the case of ródka, it is essential to discover its historical background and consider the relative isolation of ródka in the previous times. In the first half of the twentieth century, the district was perceived as a local base of crafts and small trade. Its distinctive mark were strong neighborhood ties. Can these ties – partly mythologized – now become the driving force of the revitalization?